Analysis of teaching skills in swimming and gymnastics in faculties of physical education - Jaber Hussein, Abdelsalam; Al-Shawabka, Loay Mohammad; Jamal Aloran, Hasan; Al Hammouri, Walid; Al Sharksi, Rama Mohammad; Thseen Alaskar, Waleed; Mahmoud Al-Hawari, Mohammad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The present study aimed to assess the extent to which faculty members apply effective teaching skills in swimming and gymnastics courses from the perspective of students in physical education faculties. Utilizing a descriptive method, the study involved a randomly selected sample of 195 students from the University of Jordan, Hashemite University, and Yarmouk University during the 2021/2022 academic year. A questionnaire was designed to evaluate effective teaching skills, focusing on the teacher’s management of teaching principles, the use of educational aids, and evaluation. Data analysis using SPSS (version 28) revealed that faculty members demonstrated a high level of application of effective teaching skills in both courses, with arithmetic means of 4.35 for swimming and 4.27 for gymnastics. No statistically significant differences were observed in the application of these skills based on gender, university, or course (p > 0.05). The researchers recommend providing faculty members with necessary resources and facilities to enhance the educational process and ensure it meets the highest standards.